PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Risya Hendyana, 08.05.51.0009; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2012)
The study aims to examine and analyze the influence of motivation, discipline work and work environmenton the performance of employeesat the Department of Health Semarang. Populasi in this study is Semarang Health Service employee who equal 120 people. Based on the calculation formula slovin samples in this study amounted to 54.5 roundedto 55 respondents. These research ersuse a method Random Sampling. Using quantitative and qualitative analysis that includes the Test Validity, Test Profitability, Multiple linier Regressi on and Coefficient of Determination.Techniques of data analysis in this study using multiple linear regression while hypothesis testing using test and F test Based on survey results revealed that there are positive and significant influence between motivation (X1) on the performance (Y), there isa significant and positive effect between labor discipline (X2) on the performance (Y), there are positive and not significant between the work environment (X3) on performance (Y), motivation, discipline and work environment work together have a positive and significant impact on employee performance. Based on the coefficient of determination there is the influence of motivational variables (X1), the variable of work discipline (X2), the work environment variables (X3) jointly affect the performance variable (Y) is 92.4% while the remaining7.6%.Keywords: Motivation, DisciplineWork, Work Environment, Performance.